Imaging of Biliary Infections - Catalano, Onofrio; Arellano, Ronald S. (Digestive Disease Interventions, 2017)
Biliary tract infections cover a wide spectrum of etiologies and clinical presentations. Imaging plays an important role in understanding the etiology and as well as the extent of disease. Imaging also plays a vital role in assessing treatment response once a diagnosis is established. This article will review the imaging findings of commonly encountered biliary tract infectious diseases.
Keywords: biliary infections; cholangitides; parasites; immunocompromised; echinococcal